2005
DOI: 10.1515/jpem.2005.18.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Other Disturbances of Severe Hypoglycaemia in Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Severe hypoglycaemia frequently causes fear and various disturbances in spite of active education and psychosocial support. There is a potential for increased quality of life from interventions targeted at the prevention of severe hypoglycaemia. Further research and improved strategies for the prevention of severe hypoglycaemia are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
2
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 34 publications
1
46
2
9
Order By: Relevance
“…51 A review of hypoglycaemia and diabetes noted that patients were as worried about severe hypoglycaemia as about eye disease. 52 Nordfeldt and Ludwigsson 53 reported that patients (under the age of 19) who had experienced an SH episode within the previous year had a lower quality of life, and that they regarded hypoglycaemia as a bigger problem than long-term complications. Quality of life as measured by EQ-5D (European Quality of life-5 Dimensions) median was normal (1.0) in those who had not had an SH episode within the past year, but reduced (0.85) in those who had.…”
Section: Hypoglycaemia In T1dmmentioning
confidence: 99%
“…51 A review of hypoglycaemia and diabetes noted that patients were as worried about severe hypoglycaemia as about eye disease. 52 Nordfeldt and Ludwigsson 53 reported that patients (under the age of 19) who had experienced an SH episode within the previous year had a lower quality of life, and that they regarded hypoglycaemia as a bigger problem than long-term complications. Quality of life as measured by EQ-5D (European Quality of life-5 Dimensions) median was normal (1.0) in those who had not had an SH episode within the past year, but reduced (0.85) in those who had.…”
Section: Hypoglycaemia In T1dmmentioning
confidence: 99%
“…The negative impact of severe hypoglycemia episodes on the QoL of young people was demonstrated in three studies, which involves samples ranging from less than 100 to more than 2000 young people (19,(59)(60) .…”
Section: Qol and Hypoglycemia Episodesmentioning
confidence: 99%
“…Fear of hypoglycaemia can have a negative impact on quality of life [3,4] and metabolic control [5,6], which can be detrimental to achieving improved glycaemic control. The Diabetes Control and Complications Trial showed that intensive management resulted in a significant increase in episodes of severe hypoglycaemia [7,8].…”
Section: Introductionmentioning
confidence: 99%